Визначення правового статусу ембріона - Коренга, Ю.; Korenga, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Статтю присвячено питанням визначення правого статусу ембріона людини, а саме питання надання йому статусу об’єкта або ж суб’єкта цивільних правовідносин. Здійснюється огляд національних та міжнародних правових актів, що регулюють дані питання та надаються пропозиції щодо їх вдосконалення. Ембріон є об’єктом, що створений в результаті людської діяльності у лабораторних умовах. Отже, лише визнання за ембріонами статусу речі сприятиме врегулюванню їх правового статусу за використанням ЦК України. Власниками ембріону необхідно визначати генетичних батьків, навіть у випаду перенесення такого ембріону в організм сурогатної матері. The article is devoted to the definition of the status of human embryo, namely the question of granting him the status of an object or a subject of civil legal relations. The author submits a review of national and international legal acts regulating theseissues. The article regards the question of determining the beginning of human life as the beginning of his legal protection by the state. In the study the importance is placed on the legal status of the human embryoin the context of specific legal relationships arising from the application of the assisted reproductive technologies programs. According to the author, the owners of the embryo must be genetic parents, even in the case of transferring the embryo into the body of a surrogate mother. The embryo is also treated as an object even being created in the laboratory surroundings. The author concludes that only the recognition of the embryos in the status of an object will promote the settlementof their legal status in accordance with the CivilCode of Ukraine. The author suggests the methods of improving the legal regulation of abortion and extracorporeal fertilization.
Determining the Legal Status of the Embryo
Keywords: право на життя; правоздатність; ембріон людини; правовий статус ембріона; репродуктивні права людини; right to life; legal competence; human embryo; the legal status of the embryo; reproductive human rights